Talent Identification in Sports Using the Adaptive Method of Core Indicators in Professional Athletes - Sajjadipour , Fatemeh; Peymanizad, Hossein; Mohammadkhani, Javad; Rezaei, Meysam (Journal of Foresight and Health Governance, 2025)
The present study was conducted with the aim of identifying athletic talent using the adaptive method of core indicators in professional athletes. This research is applied in terms of purpose and descriptive-analytical in terms of nature and method, utilizing a mixed-methods approach (qualitative-quantitative). The statistical population in the qualitative section included selected scientific articles from domestic and international databases, as well as academic experts and elite athletes. Sampling was conducted purposively, and data were collected through semi-structured interviews and analyzed using thematic analysis. In the quantitative section, the statistical population consisted of 36 professional and elite athletes selected using purposive sampling. Data were collected using a researcher-made questionnaire and analyzed using a one-sample t-test. The results indicated that athletic talent identification through the adaptive method of core indicators includes seven main dimensions (genetic, physiological, anthropometric, psychological, biological, living environment, and lifestyle) and 53 indicators. Of these, 46 indicators were in a favorable condition, while 7 indicators (having athlete parents, sitting height, lower limb length, pelvic width, thoracic circumference, abdominal circumference, and the use of university-educated professionals in talent identification centers) were in an unfavorable condition. The highest means were related to the indicators of intrinsic interest in competitive sports (4.47), physical health (4.42), and mental toughness (4.39). Athletic talent identification is a complex and multidimensional process that requires attention to a range of genetic, physiological, anthropometric, psychological, biological, and environmental indicators. To succeed in this process, a comprehensive and scientific talent identification system must be designed and implemented with the participation of academic experts and by considering all these indicators. Furthermore, special attention should be given to the indicators that are in an unfavorable condition, and appropriate plans should be developed to improve them.